1991
DOI: 10.1182/blood.v77.10.2169.bloodjournal77102169
|View full text |Cite
|
Sign up to set email alerts
|

The sequence gamma-(312-324) is a fibrin-specific epitope

Abstract: Fibrin accelerates the activation of plasminogen catalyzed by tissue- type plasminogen activator much stronger than fibrinogen. Detailed studies showed that (part of) this rate-enhancing effect of fibrin is brought about by two sites in the fibrin molecule: one in A alpha-(148- 160) and one in the gamma-chain stretch 311–379 (also known as FCB-5). During the fibrinogen-to-fibrin conversion, A alpha-(148–160) appears to become accessible, because a monoclonal antibody against synthetic A alpha-(148–160) reacts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 0 publications
1
43
0
Order By: Relevance
“…FCB-2 and FCB-5 are soluble substitutes for solid-phase fibrin and can accelerate t-PA mediated activation of plasminogen. Monoclonal antibodies against a part of FCB-2 (Act-( 148-160)] [32] or FCB-5 (y-(312-325)] [33] react with fibrin, but not with fibrinogen. Moreover, Aa-Lys157 of FCB-2 and y-Lys321 of FCB-5 bind to the lysine binding sites (LBS) of plasminogen and t-PA [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…FCB-2 and FCB-5 are soluble substitutes for solid-phase fibrin and can accelerate t-PA mediated activation of plasminogen. Monoclonal antibodies against a part of FCB-2 (Act-( 148-160)] [32] or FCB-5 (y-(312-325)] [33] react with fibrin, but not with fibrinogen. Moreover, Aa-Lys157 of FCB-2 and y-Lys321 of FCB-5 bind to the lysine binding sites (LBS) of plasminogen and t-PA [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Using monoclonal antibodies against either fibrinogen or fibrin, earlier studies have revealed that the D domains of fibrinogen and fibrin are immunologically distinct. [73][74][75] The central region of the gamma chain is inaccessible to antibodies in native fibrinogen 73,74 but hidden epitopes within it are exposed following platelet binding and/or enzyme degradation. 75,76 Finally, and directly pertinent to the present results, we find that the critically important P1 and P2 epitopes are displayed on both fibrin and surface-bound fibrinogen but are occult in native fibrinogen.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Fibrin degradation products, the D-D:E 1 complex and its components, dimeric D-D fragment and fragment E 1 , were prepared from plasmin digest of factor XIIIacrosslinked human fibrin. 5 Fibrin specific murine monoclonal antibodies (Mabs) against A α 148-160 and γ 312-324 regions of fibrin(ogen) 6,7 were obtained from Dr. Nieuwenhuizen. Binding studies were performed by enzyme linked immunoassay (ELISA) and by surface plasmon resonance method (SPR) using the IAsys biosensor (Fisons, Cambridge, UK) as described in References 5,8,and 9. Differential scanning calorimetry (DSC) measurements were made with DASM-4M calorimeter at a scan rate of 1 ° C/min as described elsewhere. 10 Protein concentrations varied from 1.0 to 2.0 mg/ml.…”
Section: Methodsmentioning
confidence: 99%